Characterization of the complete chloroplast genome of Prunus davidiana, an excellent horticultural species - Xi Wang; Junru Wang; Minrong Luo (Mitochondrial DNA. Part B. Resources, 2020)
Prunus davidiana (Rosaceae) is of great importance horticulturally as the rootstock of some fruit trees. Here, the complete chloroplast genome of P. davidiana was assembled based on the Illumina reads. The complete cp genome of P. davidiana was 157,660 bp in length and contained a pair of inverted repeat (IR, 26,387 bp) regions, which were separated by the small single-copy (SSC, 19,122 bp) and the large single-copy (LSC, 85,764 bp) regions. It encoded 135 genes. The phylogenetic analysis revealed that P. davidiana is sister to other peaches. This result will be useful for future studies of the lineage.